Legionnaires’ disease: an increasing risk (Italian Journal of Public Health, 2003)
Even if the pathogen of Legionnaires’ disease has been discovered thirty years ago there are many unanswered questions about it’s aetiology, epidemiology, clinical presentation and prevention.As a matter of fact, Legionnaires’ disease, as with many others infectious diseases, represents a perfect example of a multidisciplinary approach involving both medical and engineering aspects, in a variety of settings such as hospitals, hotels and thermal facilities.Issues such as these will be debated within the present meeting.